Physical activity habits in a European sports event: A case study - Leonor Gallardo; Javier Sánchez-Sánchez; Ferran Calabuig; Pablo Burillo; José Luis Felipe; Álvaro Fernández-Luna (Universidade Estadual Paulista (UNESP), 2014)
The aim of this study is to learn more about the physical activity habits of participants in a popular sporting event such as European Sports Day, which is held simultaneously in five European countries (Spain, Italy, Cyprus, Ireland, and Hungary), and to measure the influence of socio-demographic variables on these habits. This is a cross-sectional study conducted with a sample of 856 participants, stratified by gender, age, and nationality. We statistically analyzed five variables related to physical activity habits: frequency of physical activity practice, places of practice, motives of practice, perceived fitness level, and popular event attendance. Of the participants, 76.8% said they perform physical activity weekly. Fitness/health improvement (34.63%) and entertainment/leisure (26.52%) are the main reasons for the practice of physical activity. Age and nationality are differentiating factors on physical activity habits.